Statistical hypothesis testing and common misinterpretations: Should we abandon p-value in forensic science applications?. (February 2016) - Taroni, F.; Biedermann, A.; Bozza, S.
Abstract : Highlights: The inferential problem: frequentist and Bayesian school of thought. Opposite views to hypothesis testing. Editorial decision to reject any paper containing null hypothesis procedures. Relevant limitations of p -value in the forensic context. Should we abandon p -value in forensic science applications? Abstract: Many people regard the concept of hypothesis testing as fundamental to inferential statistics. Various schools of thought, in particular frequentist and Bayesian, have promoted radically different solutions for taking a decision about the plausibility of competing hypotheses. Comprehensive philosophical comparisons about their advantages and drawbacks are widely available and continue to span over large debates in the literature. More recently, controversial discussion was initiated by an editorial decision of a scientific journal[1] to refuse any paper submitted for publication containing null hypothesis testing procedures. Since the large majority of papers published in forensic journals propose the evaluation of statistical evidence based on the so called p -values, it is of interest to expose the discussion of this journal's decision within the forensic science community. This paper aims to provide forensic science researchers with a primer on the main concepts and their implications for making informed methodological choices.